Deashing adsorption filler, preparation method and application of deashing adsorption filler in polyolefin deashing
By using deaze-adsorbing fillers composed of epoxy quaternary ammonium salts and metal oxides, the problem of difficult metal residue removal in polyolefin production is solved, and the efficient and low-cost metal removal effect is achieved, and the purity and performance of polyolefin materials are improved.
Patent Information
- Application Number
- CN202411795969.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-14
AI Technical Summary
The prior art is difficult to effectively remove metal residues in the polyolefin production process, resulting in the impact of the material color, optical properties and electrical properties, and the existing ash deaeration method is cumbersome, low efficiency and high cost.
A deaze-adsorption filler containing epoxy quaternary ammonium salt and metal oxide is prepared by impregnation loading method for chelating adsorption and deaze of polyolefin solution, improving adsorption efficiency and significantly reducing metal residue.
It realizes efficient removal of metal residues in polyolefin solution, reduces metal residues to below 1 ppm, improves material purity, simplifies the process, and reduces costs.
Smart Images

Figure BDA0005176706680000091 
Figure BDA0005176706680000101
Abstract
Description
Technical Field
[0001] The invention relates to a deashing adsorption filler, in particular to a deashing adsorption filler for polyolefin, a preparation method and application thereof. Background Art
[0002] In recent years, with the continuous maturity of the polymer market, the global polyolefin business has become increasingly perfect, and polyolefin products have developed rapidly towards high-end, differentiated and diversified development, and are widely used in the automotive field, rail transit field, medical device field, consumer electronics field, high-end optics field and electronic communications field.
[0003] Common polyolefin products are mostly produced by solution polymerization, and metal catalysts are required in the production process. The metal components contained in the catalysts remain in the polyolefin products, which will have an adverse effect on the color, optical properties, electrical and electronic properties of the polymer materials and the final products, and will also cause metal pollution, etc. Therefore, how to deash the polyolefin solution to reduce the metal residue in the material and improve the purity of the polyolefin material is one of the key processes for developing high-end polyolefin products.
[0004] The deashing methods commonly used in polymer industrial production at present include coagulation precipitation method, aqueous phase extraction method and chelate adsorption method. For example, butadiene rubber (BR) and isoprene rubber (IR) use coagulants to make residual metals form insoluble metal compounds for removal during production. This method has complicated process, phase separation difficulty and easy clogging equipment. Ethylene propylene diene monomer (EPDM) and styrene elastomer use hot alkaline water washing and extraction to remove metals during production. This method has complicated steps and low removal efficiency. The production process of materials such as linear low-density polyethylene (LLDPE) and cycloolefin-ethylene copolymer (COC) uses chelate adsorption to remove metals, but the current chelate adsorption needs to be carried out under high temperature conditions, has the disadvantages of large equipment investment and high production cost, and is difficult to remove metals to less than 5ppm, and the adsorbent adsorption efficiency is difficult to further improve. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a deashing adsorption filler and a preparation method thereof, comprising metal oxides and epoxy quaternary ammonium salts, which can be widely used in the field of metal removal from polymer solutions and have versatility and high efficiency.
[0006] The present invention also provides application of the deashing adsorption filler in the field of polyolefins, which is used for chelating adsorption deashing of polyolefin solutions, thereby improving adsorption efficiency and significantly reducing metal residues.
[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0008] On the one hand, the present invention provides a deashing adsorption filler, comprising an epoxy quaternary ammonium salt and a metal oxide, wherein the mass content of the epoxy quaternary ammonium salt accounts for 0.1-10% of the mass of the deashing adsorbent, for example, 0.1%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc., preferably 1-5%; the mass content of the metal oxide accounts for 90-99.9% of the mass of the deashing adsorbent, for example, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, 99.9%, etc., preferably 95-99%, and the sum of the mass contents of the epoxy quaternary ammonium salt and the metal oxide is 100%.
[0009] Further, in a specific embodiment of the present invention, the epoxy quaternary ammonium salt is selected from one or more of glycidyl dimethyl dodecyl ammonium chloride, diethyl-2,3-epoxypropyl-3-(methyldimethoxy)silylpropyl ammonium chloride, hexafluoropropylene oxide trimer quaternary ammonium salt iodide, and 2,3-epoxypropyltrimethylammonium chloride, preferably 2,3-epoxypropyltrimethylammonium chloride.
[0010] Furthermore, in a specific embodiment of the present invention, the metal oxide is an inorganic metal oxide, preferably an alkaline metal oxide and / or a neutral metal oxide, more preferably one or more of aluminum oxide, zinc oxide, copper oxide, chromium oxide, sodium oxide, magnesium oxide, and calcium oxide.
[0011] Furthermore, in a specific embodiment of the present invention, the specific surface area of the deashing adsorption filler is 50-500m 2 / g, for example 50m 2 / g、100m 2 / g, 150m 2 / g, 200m 2 / g, 250m 2 / g, for example 300m 2 / g, 350m 2 / g, 400m 2 / g, 450m 2 / g、500m 2 / g, etc., preferably 200-300m 2 / g; and / or
[0012] The pore volume of the deashing adsorption filler is 0.1-2m 3 / g, for example 0.1m 3 / g, 0.3m 3 / g, 0.5m 3 / g, 0.7m 3 / g, 0.9m 3 / g, 1m 3 / g, 1.2m3 / g, 1.4m 3 / g, 1.6m 3 / g, 1.8m 3 / g, 2m 3 / g, etc., preferably 0.2-1m 3 / g; and / or
[0013] The average pore distance of the deashing adsorption filler is 0.1-20 nm, for example, 0.1 nm, 1 nm, 3 nm, 5 nm, 7 nm, 9 nm, 10 nm, 12 nm, 14 nm, 16 nm, 18 nm, 20 nm, etc., preferably 1-10 nm.
[0014] On the other hand, the present invention also provides a method for preparing the deashing adsorption filler.
[0015] The deashing adsorption filler as described above can be prepared by conventional methods in the art, such as impregnation loading and the like. The operation and process conditions in the preparation method of the present invention, and the devices used therein, can all be carried out by the corresponding conventional selections in the art, and there are no particular restrictions on this. Technicians can optimize the known processes based on the prior art according to actual needs. Specifically, for example, the conditions listed in the following embodiments of the present invention can be adopted.
[0016] Specifically, a method for preparing the deashing adsorption filler as described above comprises the following steps:
[0017] 1) adding epoxy quaternary ammonium salt to water and stirring to obtain epoxy quaternary ammonium salt aqueous solution;
[0018] 2) The surface of the metal oxide is impregnated with an aqueous solution of epoxy quaternary ammonium salt and dried to obtain the deashing adsorption filler.
[0019] Further, in a specific embodiment of the present invention, in step 1), the amount of water used is 1-10 times the mass of the metal hydroxide, such as 1 time, 3 times, 5 times, 7 times, 9 times, 10 times, etc., preferably 2-4 times.
[0020] Further, in a specific embodiment of the present invention, in step 1), the temperature condition for dissolving the epoxy quaternary ammonium salt is 20-100°C, such as 20°C, 40°C, 60°C, 80°C, 90°C, 100°C, etc., preferably 40-80°C.
[0021] Furthermore, in a specific embodiment of the present invention, in step 2), the mass ratio of the metal oxide to the epoxy quaternary ammonium salt in step 1) is 1:0.001-0.1, for example, 1:0.001, 1:0.005, 1:0.01, 1:0.03, 1:0.05, 1:0.07, 1:0.09, 1:0.1, etc.
[0022] Further, in a specific embodiment of the present invention, in step 2), the method of impregnating the metal oxide with an aqueous solution of an epoxy quaternary ammonium salt is a conventional operation in the field, for example, the aqueous solution of an epoxy quaternary ammonium salt can be uniformly dripped onto the surface of the metal oxide, and then impregnated for a certain period of time, and the time of the impregnation treatment is 1-36 hours, for example, 1 hour, 5 hours, 8 hours, 12 hours, 18 hours, 24 hours, 30 hours, 36 hours, etc., preferably 8-12 hours;
[0023] There is no particular requirement for the immersion treatment temperature, which may be 10-80°C, such as 10°C, 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, etc., preferably 30-60°C, and it is usually carried out at room temperature.
[0024] Further, in a specific embodiment of the present invention, in step 2), the drying is a conventional operation in the field, preferably, the temperature is 60-120°C, for example, 60°C, 80°C, 100°C, 110°C, 120°C, etc., preferably 80-110°C; there is no special requirement for the drying time, which can be 6-24h, for example, 6h, 12h, 18h, 24h, etc., preferably 12-20h, until constant weight is obtained.
[0025] In another aspect, the present invention further provides a use of the deashing adsorption filler in deashing of polymer solutions, which is particularly suitable as a deashing adsorption filler dedicated to polyolefins.
[0026] Specifically, the present invention provides an application of a deashing adsorption filler as described above or a deashing adsorption filler prepared by the method described above in the deashing of polyolefins. For example, the deashing adsorbent provided by the present invention can be used for the efficient removal of residual metals in cycloolefin copolymer (COC) reaction solution, polyolefin elastomer (POE) reaction solution, styrene-butadiene rubber (SBR) reaction solution, ethylene-propylene-diene rubber (EPDM) reaction solution, etc. The residual metal elements that can be removed include aluminum, magnesium, iron, sodium, zirconium, titanium, etc., and the residual metal content can be reduced to below 1 ppm (below the detection limit).
[0027] The application of the deashing adsorbent involved in the present invention in the deashing of polyolefins is an existing process. For its related operations and process conditions, and the devices used, technicians can optimize them according to actual needs based on the known processes in the prior art. For example, the specific application method listed below in the present invention can be adopted, including: filling the deashing adsorption filler into the adsorption column, heating the adsorption column to 50-150°C, then passing the polyolefin solution into the adsorption column, adjusting the liquid flow rate to 5-10mL / min, and collecting the effluent, which is the deashed and purified polyolefin solution.
[0028] In practical applications, before the polyolefin solution is passed into the adsorption column for adsorption, the polyolefin solution is first mixed with a chelating agent and heated to perform a chelating reaction;
[0029] Preferably, the amount of the chelating agent added is 1-20 times, preferably 1-10 times, more preferably 3-5 times the molar content of the residual metal in the polyolefin solution;
[0030] Preferably, the chelating agent is a C4-C9 diketone, preferably diacetyl, 2,3-pentanedione, 2,4-pentanedione, 2,3-hexanedione, 2,4-hexanedione, 3,4-hexanedione, 2,3-heptanedione, 2,6-heptanedione, 3,5-heptanedione, 2,3-octanedione, 2,4-nonanedione, more preferably 2,3-pentanedione, 2,4-pentanedione, 2,3
[0031] -Hexanedione, 2,4-hexanedione, 3,4-hexanedione.
[0032] Preferably, the chelating reaction is carried out at a temperature of 100-300°C and a time of 1-10 min. Compared with the prior art, the beneficial effects of the technical solution of the present invention are mainly reflected in the following aspects:
[0033] (1) In the devolatilization adsorption filler of the present invention, the epoxy quaternary ammonium salt is loaded on the surface of the metal oxide, which can effectively increase the number of positive charges on the surface of the metal oxide and greatly improve the adsorption efficiency of the metal oxide for the metal complex.
[0034] (2) The deashing adsorption filler of the present invention can efficiently adsorb the residual metal in the polyolefin solution, and can remove the metal residue in the polyolefin solution to 1 ppm. Compared with the traditional chelating adsorption method, it has low adsorption temperature, high deashing efficiency, large adsorption capacity, low swelling, low solution pressure drop, simple preparation process and low cost;
[0035] (3) The deashing adsorbent of the present invention can be widely used in the field of metal removal from polymer solutions, and is suitable for the removal of residual metals in a variety of polyolefin solutions. It has versatility and high efficiency, and has a very broad application prospect. DETAILED DESCRIPTION
[0036] The present invention is further described below by means of specific examples. The examples described in the present invention are only used to illustrate the present invention and do not limit the scope of the present invention.
[0037] In the embodiments and comparative examples of the present invention, the sources of the main raw materials used are as follows. Unless otherwise specified, other raw materials and reagents were purchased from commercial sources:
[0038] Magnesium oxide, zinc oxide, calcium oxide, aluminum oxide, 3,4-epoxycyclohexylcarboxylate, epoxypropyl dimethyl dodecyl ammonium chloride, diethyl-2,3-epoxypropyl-3-(methyldimethoxy)silylpropyl ammonium chloride, hexafluoropropylene oxide trimer quaternary ammonium salt iodide, 2,3-epoxypropyl trimethyl ammonium chloride, methyl tri(hexadecyl) ammonium salt, 2,4-pentanedione, 2,3-pentanedione, 2,3-hexanedione, 2,4-hexanedione, 2,3-heptanedione, toluene, hexane, cyclohexane, ethanol, octene, and triisobutylaluminum were all purchased from Alfa Aesar Chemicals.
[0039] rac-dimethylsilylbisindenyl zirconium dichloride was purchased from Beijing Inokai Technology Co., Ltd.;
[0040] Methylaluminoxane (MAO) was purchased from Chemtura Organometallics;
[0041] 2-Norbornene (NBE) was purchased from Tokyo Chemical Industry Co., Ltd. (TCI);
[0042] Ethylene norbornene (ENB) was purchased from Tokyo Chemical Industry Co., Ltd. (TCI);
[0043] Styrene was purchased from Sinopec Qilu Petrochemical Co., Ltd.;
[0044] Ethylene, propylene and butadiene were purchased from Air Liquide (Shanghai) Compressed Gas Co., Ltd.
[0045] The main testing methods involved in the present invention are as follows:
[0046] Specific surface area and pore size of the adsorbent: Micromeritics ASAP 2420 was used to test nitrogen adsorption and desorption at 77K.
[0047] Adsorbent density: tested using Japan Shimadzu high-precision electronic density analysis balance AUY120.
[0048] Aluminum content in the sample: tested by Agilent inductively coupled plasma emission spectrometer (ICP), Agilent 8900, dual quadrupole detector, four-channel reaction cell for element qualitative and quantitative analysis.
[0049] Adsorption column: Cylindrical adsorption column, made of 316L stainless steel, with dimensions of 40×400mm and a volume of approximately 500mL.
[0050] The residence time of the polymer solution in the adsorption column is calculated as follows:
[0051] Residence time = (adsorption column volume - adsorbent effective filling volume) / polymer solution flow rate; wherein, adsorbent effective filling volume = adsorbent mass / adsorbent density.
[0052] Unless otherwise specified, the pressure conditions in the following embodiments are gauge pressure.
[0053] The steps for preparing the polymer reaction solution are as follows:
[0054] (1) Preparation of COC reaction liquid: 500 g of 2-norbornene and 2 L of purified toluene were added to a 5 L reactor, the reactor was heated to 70°C, and high-purity ethylene was introduced into the reactor until the pressure reached 0.5 MPa. After the pressure was balanced, 0.74 g of MAO and 4.5 mg of rac-dimethylsilylbisindenyl zirconium dichloride were added into the reactor through the feed bin to initiate polymerization. After 5 minutes of reaction, 1 mL of ethanol was added into the reactor through the feed bin and stirring was continued for 5 min to obtain COC reaction liquid. The discharge valve at the bottom of the reactor was opened, 10 mL of COC reaction liquid was added to 10 mL of ethanol to precipitate COC solid, and the solid was placed in a vacuum oven at 70°C and dried for 24 h. The aluminum content in the solid was 14291 ppm as determined by ICP test.
[0055] (2) Preparation of POE reaction liquid: 300 g of octene and 2 L of purified toluene were added to a 5 L reactor, the reactor was heated to 100 ° C, and then high-purity ethylene was introduced into the reactor until the pressure reached 3 MPa. After the pressure was balanced, 0.74 g of MAO and 4.5 mg of rac-dimethylsilylbisindenyl zirconium dichloride were added into the reactor through the feed bin to initiate polymerization. After 5 minutes of reaction, 1 mL of ethanol was added into the reactor through the feed bin and continued to stir for 5 min to obtain POE reaction liquid. The discharge valve at the bottom of the reactor was opened, 10 mL of POE reaction liquid was added to 10 mL of ethanol to precipitate POE solid, and the solid was placed in a vacuum oven at 70 ° C and dried for 24 h. The aluminum content in the solid was 9826 ppm as determined by ICP test.
[0056] (3) Preparation of LLDPE reaction liquid: 50 g of octene and 2 L of refined hexane were added to a 5 L reactor, the reactor was heated to 100 °C, and then high-purity ethylene was introduced into the reactor until the pressure reached 3 MPa. After the pressure was balanced, 0.74 g of MAO and 4.5 mg of rac-dimethylsilylbisindenyl zirconium dichloride were added into the reactor through the feed bin to initiate polymerization. After 5 minutes of reaction, 1 mL of ethanol was added into the reactor through the feed bin and stirring was continued for 5 min to obtain LLDPE reaction liquid. The discharge valve at the bottom of the reactor was opened, 10 mL of LLDPE reaction liquid was taken and 10 mL of ethanol was added to precipitate LLDPE solid, which was placed in a vacuum oven at 70 °C and dried for 24 h. The aluminum content in the solid was 9932 ppm according to ICP test.
[0057] (4) Preparation of EPDM solution: Add 10g of ENB and 2L of refined hexane to a 5L reactor, heat the reactor to 80°C, and then introduce high-purity ethylene and propylene into the reactor at a flow ratio of 2:1 until the pressure reaches 0.8MPa. After the pressure is balanced, add 0.74g of MAO and 4.5mg of rac-dimethylsilylbisindenyl zirconium dichloride into the reactor through the feed bin to initiate polymerization. After reacting for 5 minutes, add 1mL of ethanol into the reactor through the feed bin and continue stirring for 5 minutes to obtain EPDM reaction solution. Open the discharge valve at the bottom of the reactor, take 10mL of EPDM reaction solution and add 10mL of ethanol to precipitate EPDM solid, put it in a vacuum oven at 70°C and dry it for 24 hours. ICP test shows that the aluminum content in the solid is 9987ppm.
[0058] (5) Preparation of SBR solution: 80 g of styrene and 2 L of refined cyclohexane were added to a 5 L reactor, the reactor was heated to 70 °C, and then high-purity butadiene was introduced into the reactor until the pressure reached 3 MPa. After the pressure was balanced, 0.74 g of MAO and 4.5 mg of rac-dimethylsilylbisindenyl zirconium dichloride were added into the reactor through the feeding bin to initiate polymerization. After the reaction for 5 min, 1 mL of ethanol was added into the reactor through the feeding bin and stirred for 5 min to obtain SBR reaction solution. The discharge valve at the bottom of the reactor was opened, 10 mL of SBR reaction solution was added to 10 mL of ethanol to precipitate SBR solid, which was placed in a 70 °C vacuum oven and dried for 24 h. The aluminum content in the solid was 10021 ppm according to ICP test.
[0059] [Example 1]
[0060] Preparation of deashing adsorption filler-1:
[0061] 0.04 kg of epoxypropyl dimethyl dodecyl ammonium chloride and 3.8 kg of deionized water were added to a beaker and stirred evenly at 60° C. The epoxypropyl dimethyl dodecyl ammonium chloride aqueous solution was evenly dripped onto the surface of 3.8 kg of calcium oxide, immersed at room temperature for 6 hours, and then dried naturally in an oven at 80° C. to obtain deashing adsorption filler-1.
[0062] In this adsorbent, the mass content of epoxypropyl dimethyl dodecyl ammonium chloride is 1.04%, and the specific surface area is 255m 2 / g, pore volume is 0.42m 3 / g, average pore size is 5.33nm, density is 1.869g / cm 3 .
[0063] [Example 2]
[0064] Preparation of deashing adsorption filler-2:
[0065] 0.08 kg of diethyl-2,3-epoxypropyl-3-(methyldimethoxy)silyl ammonium chloride and 5.7 kg of deionized water were added to a beaker and stirred evenly at 70°C. The diethyl-2,3-epoxypropyl-3-(methyldimethoxy)silyl ammonium chloride aqueous solution was evenly dripped onto the surface of 3.8 kg of zinc oxide, immersed at room temperature for 12 hours, and dried in a 90°C oven to constant weight to obtain deashing adsorption filler-2.
[0066] In the adsorbent, the mass content of diethyl-2,3-epoxypropyl-3-(methyldimethoxy)silylpropyl ammonium chloride is 2.1%, and the specific surface area is 248m 2 / g, pore volume is 0.38m 3 / g, average pore size is 5.13nm, density is 1.835g / cm 3 .
[0067] [Example 3]
[0068] Preparation of deashing adsorption filler-3:
[0069] 0.12 kg of hexafluoropropylene oxide trimer quaternary ammonium salt iodide and 7.6 kg of deionized water were put into a beaker and stirred evenly at 80° C. The hexafluoropropylene oxide trimer quaternary ammonium salt iodide aqueous solution was evenly dripped onto the surface of 3.8 kg of magnesium oxide, immersed at room temperature for 18 hours, and dried in an oven at 100° C. to constant weight to obtain deashing adsorption filler-3.
[0070] In the adsorbent, the mass content of hexafluoropropylene oxide trimer quaternary ammonium salt iodide accounts for 3.06%, and the specific surface area is 241m 2 / g, pore volume is 0.34m 3 / g, average pore size is 5.06nm, density is 1.812g / cm 3 .
[0071] [Example 4]
[0072] Preparation of deashing adsorption filler-4:
[0073] 0.2 kg of 2,3-epoxypropyltrimethylammonium chloride and 9.5 kg of deionized water were added to a beaker and stirred evenly at 90° C. The 2,3-epoxypropyltrimethylammonium chloride aqueous solution was evenly dripped onto the surface of 3.8 kg of alumina, immersed at room temperature for 24 hours, and dried in an oven at 110° C. to constant weight, thereby obtaining deashing adsorption filler-4.
[0074] In the adsorbent, the mass content of 2,3-epoxypropyltrimethylammonium chloride is 5.00%, and the specific surface area is 231m 2 / g, pore volume is 0.31m 3 / g, average pore size is 5.00nm, density is 1.801g / cm 3 .
[0075] Comparative Example 1
[0076] Deashing adsorption filler-5 was prepared by referring to the method of Example 1, except that: the amount of 2,3-epoxypropyltrimethylammonium chloride raw material was replaced with 0.95 kg, and other operations and conditions remained unchanged to obtain adsorption filler-5, wherein the mass content of 2,3-epoxypropyltrimethylammonium chloride accounted for 20%, and the specific surface area was 182 m 2 / g, pore volume is 0.14m 3 / g, average pore size is 2.45nm, density is 1.673g / cm 3 .
[0077] Comparative Example 2
[0078] Deashing adsorption filler-6 was prepared by referring to the method of Example 1, except that: the epoxy quaternary ammonium salt was replaced by an equal amount of methyl tri(hexadecyl)ammonium salt (non-epoxy quaternary ammonium salt) instead of 2,3-epoxypropyltrimethylammonium chloride, and other operations and conditions remained unchanged to obtain adsorption filler-6.
[0079] Comparative Example 3
[0080] Deashing adsorption filler-7 was prepared by referring to the method of Example 1, except that: the epoxy quaternary ammonium salt was replaced by an equal amount of 3,4-epoxycyclohexylcarboxylate (non-epoxy quaternary ammonium salt) instead of 2,3-epoxypropyltrimethylammonium chloride, and other operations and conditions remained unchanged to obtain adsorption filler-7.
[0081] Comparative Example 4
[0082] Deashing adsorption filler-8 was prepared by referring to the method of Example 1, except that the metal oxide was replaced by an equal amount of activated carbon instead of alumina, and other operations and conditions remained unchanged to obtain adsorption filler-8.
[0083] Comparative Example 5
[0084] Deashing adsorption filler-9 was prepared by referring to the method of Example 1, except that the metal oxide was replaced by an equal amount of diatomaceous earth instead of alumina, and other operations and conditions remained unchanged to obtain adsorption filler-9.
[0085] The deashing adsorption filler prepared in Example 1-4 is applied to remove residual metallic aluminum in a polyolefin solution, and the steps are as follows:
[0086] The COC reaction solution prepared in the previous article was added to the chelating kettle, and 2,4-pentanedione was added at a molar ratio of 6 times the residual metal aluminum content in the solution. The temperature was raised to 150°C, and chelated for 5 minutes. The deashing adsorption fillers 1-4 prepared in each embodiment were respectively filled into the adsorption column, and the effective filling volume of the adsorbent was 450mL. The adsorption column was heated, and the COC reaction solution, POE reaction solution, LLDPE reaction solution, EPDM reaction solution, and SBR reaction solution after the chelating reaction were respectively passed through, and the flow rate of each polymer solution was adjusted to 10mL / min by a liquid flowmeter. The same volume of ethanol was added to each polymer solution flowing out of the adsorption column, and the polymer was precipitated. After filtering, it was placed in a vacuum oven at 80°C and dried for 24 hours. The aluminum content was tested by ICP and recorded in Table 1.
[0087] The above deashing operation was repeated on the POE reaction solution, LLDPE reaction solution, EPDM reaction solution and SBR reaction solution prepared above, wherein 2,3-pentanedione, 2,3-hexanedione, 2,4-hexanedione and 2,3-heptanedione were used as chelating agents, respectively, and the chelation reaction temperatures were 125°C, 100°C, 75°C and 50°C, respectively. Other operations and conditions remained unchanged. The adsorption column treatment conditions and results are shown in Table 1.
[0088] In addition, the above-mentioned adsorption operation of the polymer solution was repeated using alumina and the deashing adsorption fillers 5-9 prepared in Comparative Examples 1-5. The test results are shown in Table 1.
[0089] Table 1 Adsorption column treatment conditions and results
[0090]
[0091]
[0092] It can be seen from the above test results that the deashing adsorption fillers prepared in each embodiment of the present invention have a significant removal effect on the residual metal content in each polymer solution. The solution of using aluminum oxide as the adsorption filler in the comparative example has a very limited removal effect on metallic aluminum.
[0093] The above is only a preferred embodiment of the present invention. It should be pointed out that ordinary technicians in this field can make several improvements and supplements without departing from the method of the present invention. These improvements and supplements should also be regarded as the scope of protection of the present invention.
Claims
1. A deashing adsorption filler, characterized in that: It comprises epoxy quaternary ammonium salt and metal oxide, wherein the mass content of the epoxy quaternary ammonium salt accounts for 0.1-10% of the mass of the deashing adsorption filler, preferably 1-5%; the mass content of the metal oxide accounts for 90-99.9% of the mass of the deashing adsorption filler, preferably 95-99%.
2. The deashing adsorption filler according to claim 1, characterized in that: The epoxy quaternary ammonium salt is selected from one or more of epoxypropyl dimethyl dodecyl ammonium chloride, diethyl-2,3-epoxypropyl-3-(methyldimethoxy)silylpropyl ammonium chloride, hexafluoropropylene oxide trimer quaternary ammonium salt iodide, and 2,3-epoxypropyl trimethyl ammonium chloride, preferably 2,3-epoxypropyl trimethyl ammonium chloride.
3. The deashing adsorption filler according to claim 2, characterized in that: The metal oxide is an inorganic metal oxide, preferably an alkaline metal oxide and / or a neutral metal oxide, more preferably one or more of aluminum oxide, zinc oxide, copper oxide, chromium oxide, sodium oxide, magnesium oxide, and calcium oxide.
4. The deashing adsorption filler according to any one of claims 1 to 3, characterized in that: The specific surface area of the deashing filler is 50-500m 2 / g, preferably 200-300m 2 / g; and / or The pore volume of the deashing filler is 0.1-2m 3 / g, preferably 0.2-1m 3 / g; and / or The average pore distance of the deashing filler is 0.1-20 nm, preferably 1-10 nm.
5. A method for preparing a deashing adsorption filler according to any one of claims 1 to 4, characterized in that: The following steps are involved: 1) adding epoxy quaternary ammonium salt to water and stirring to obtain epoxy quaternary ammonium salt aqueous solution; 2) The surface of the metal oxide is impregnated with an aqueous solution of epoxy quaternary ammonium salt and dried to obtain the deashing adsorption filler.
6. The preparation method according to claim 5, characterized in that: In step 1), the amount of water used is 1-10 times, preferably 2-4 times, the amount of the metal hydroxide.
7. The preparation method according to claim 5 or 6, characterized in that: In step 1), the temperature condition for dissolving the epoxy quaternary ammonium salt is 20-100°C, preferably 40-80°C.
8. The preparation method according to claim 7, characterized in that: In step 2), the mass ratio of the metal oxide to the epoxy quaternary ammonium salt in step 1) is 1:0.001-0.
1.
9. The method for preparing the deashing adsorption filler for polyolefin according to claim 8, characterized in that: In step 2), the immersion time is 1-36 hours, preferably 8-12 hours; In step 2), the drying temperature is 60-120°C, preferably 80-110°C.
10. Use of the deashing adsorption filler according to any one of claims 1 to 4 or the deashing adsorption filler prepared by the method according to any one of claims 5 to 9 in deashing polyolefins.